Air quality improvements and health benefits from China's clean air action since 2013. (7th November 2017) - Zheng, Yixuan; Xue, Tao; Zhang, Qiang; Geng, Guannan; Tong, Dan; Li, Xin; He, Kebin
Abstract: Aggressive emission control measures were taken by the Chinese government after the promulgation of the 'Air Pollution Prevention and Control Action Plan' in 2013. Here we evaluated the air quality and health benefits associated with this stringent policy during 2013–2015 by using surface PM2.5 concentrations estimated from a three-stage data fusion model and cause-specific integrated exposure–response functions. The population-weighted annual mean PM2.5 concentrations decreased by 21.5% over China during 2013–2015, reducing from 60.5 in 2013 to 47.5 μg m −3 in 2015. Subsequently, the national PM2.5 -attributable mortality decreased from 1.22 million (95% CI: 1.05, 1.37) in 2013 to 1.10 million (95% CI: 0.95, 1.25) in 2015, which is a 9.1% reduction. The limited health benefits compared to air quality improvements are mainly due to the supralinear responses of mortality to PM2.5 over the high concentration end of the concentration–response functions. Our study affirms the effectiveness of China's recent air quality policy; however, due to the nonlinear responses of mortality to PM2.5 variations, current policies should remain in place and more stringent measures should be implemented to protect public health.